Tooth Clenching Induces Abnormal Cerebrovascular Responses in Migraineurs - Nina Zaproudina; Antti-Pekka E. Rissanen. Jukka A. Lipponen; Anu Vierola; Saara M. Rissanen; Pasi A. Karjalainen; Seppo Soinila; Matti Närhi (FRONTIERS MEDIA SA, 2022)
Prevalence of masticatory parafunctions, such as tooth clenching and grinding, is higher among migraineurs than non-migraineurs, and masticatory dysfunctions may aggravate migraine. Migraine predisposes to cerebrovascular disturbances, possibly due to impaired autonomic vasoregulation, and sensitization of the trigeminovascular system. The relationships between clenching, migraine, and cerebral circulation are poorly understood. We used Near-Infrared Spectroscopy to investigate bilateral relative oxy-(Þlta[O(2)Hb]), deoxy-(Þlta[HHb]), and total (Þlta[tHb]) hemoglobin concentration changes in prefrontal cortex induced by maximal tooth clenching in twelve headache-free migraineurs and fourteen control subjects. From the start of the test, migraineurs showed a greater relative increase in right-side Þlta[HHb] than controls, who showed varying reactions, and right-side increase in Þlta[tHb] was also greater in migraineurs (p < 0.001 and p < 0.05, respectively, time-group interactions, Linear mixed models). With multivariate regression model, migraine predicted the magnitude of maximal blood pressure increases, associated in migraineurs with mood scores and an intensity of both headache and painful signs of temporomandibular disorders (pTMD). Although changes in circulatory parameters predicted maximal NIRS responses, the between-group differences in the right-side NIRS findings remained significant after adjusting them for systolic blood pressure and heart rate. A family history of migraine, reported by all migraineurs and four controls, also predicted maximal increases in both Þlta[HHb]and Þlta[tHb]. Presence of pTMD, revealed in clinical oral examination in eight migraineurs and eight controls, was related to maximal Þlta[HHb] increase only in controls. To conclude, the greater prefrontal right-side increases in cerebral Þlta[HHb] and Þlta[tHb] may reflect disturbance of the tooth clenching-related cerebral (de)oxygenation based on impaired reactivity and abnormal microcirculation processes in migraineurs. This finding may have an impact in migraine pathophysiology and help to explain the deleterious effect of masticatory dysfunctions in migraine patients. However, the role of tooth clenching as a migraine trigger calls for further studies.